2012
DOI: 10.2753/ree1540-496x480204
|View full text |Cite
|
Sign up to set email alerts
|

Short- and Long-Term Performance of Polish IPOs

Abstract: The paper documents short-and long-run performance of initial public offerings on the Warsaw Stock Exchange from 1998 to 2008. The study reveals positive initial market-adjusted returns of 13.95 percent and significant long-term underperformance with mean of -22.62 percent for the three-year buy-and-hold strategy. We introduce ordinary least squares regressions to find determinants of initial returns. Our findings document strong explanatory power of early aftermarket volatility, issuer's size, growth opportun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
25
0
4

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 39 publications
(29 citation statements)
references
References 29 publications
0
25
0
4
Order By: Relevance
“…This observation contradicts the information asymmetry theory. These results are supported by Jewartowski and Lizinska (2012). The authors studied the short and long-term performance of IPOs in Poland between the years 2000-2008.…”
Section: Introductionmentioning
confidence: 62%
“…This observation contradicts the information asymmetry theory. These results are supported by Jewartowski and Lizinska (2012). The authors studied the short and long-term performance of IPOs in Poland between the years 2000-2008.…”
Section: Introductionmentioning
confidence: 62%
“…Studies in many countries confirmed the phenomenon of the aboveaverage rate of return on the shares purchased in the offer and sold on the first day of IPO (Ritter and Welch, 2002;Loughran, Ritter and Rydqvist, 1994). This phenomenon was also confirmed for the Polish market (Jewartowski and Lizi ska, 2012;Sieradzki, 2013;Gemzik-Salwach and Perz, 2013). A large difference between the IPO and the sales price of shares means that the company could sell itself for more, acquiring more resources; in the English literature, the money that could potentially be acquired (during the sales of shares at IPO prices) is referred to as "money left on the table".…”
Section: Literature Reviewmentioning
confidence: 57%
“…On the Polish stock market, the long-term operating underperformance was noted by Dudycz (2013). The market underperformance of IPO firms that went public on the Polish stock market was documented by Jelic and Briston (2003), Jewartowski and Lizińska (2012), and Lizińska and Czapiewski (2014).…”
Section: Literature Review and Research Hypothesesmentioning
confidence: 99%